The Influence of Leadership Style, Organizational Culture and Organizational Justice on Employee Performance at the Regional Representative Office of Bank Indonesia Jember - Indah Lestari; Hari Sulaksono; Tamriatin Hidayah (International Journal of Economics, Commerce, and Management, 2025)
This study aims to test and analyze the influence of leadership style , organizational culture and organizational justice partially and simultaneously on the performance of employees of the Bank Indonesia Jember Representative Office. The population in this study were all employees of Bank Indonesia Jember with a sampling technique of saturated sampling technique totaling 42 employees. The analysis method used is multiple linear regression analysis. Based on the results of the data analysis, it shows that partially, leadership style does not have a significant effect on employee performance. However, certain aspects such as decision making, motivation, communication, employee control, and emotional control play an important role. Improvements in this aspect can support performance indirectly. Organizational culture significantly affects employee performance. Self-awareness, aggressiveness, personality, performance, and team orientation play a role in creating a productive work environment. Organizational justice does not significantly affect employee performance. Indicators such as resource allocation, procedural fairness, and personal relationships play an important role. The three variables ( leadership style , organizational culture, and organizational justice) together affect employee performance. In addition, the researcher's suggestions for further research are expected to complement the limitations of the researcher's problems such as increasing the number of samples, for example all employees of KpwBI Jember, or adding independent variables to be studied, for example motivation, discipline, workload, occupational health and work life balance.